Acoustically Triggered Disassembly of Multilayered Polyelectrolyte Thin Films through Gigahertz Resonators for Controlled Drug Release Applications - Zhixin Zhang; Zifan Tang; Wenpeng Liu; Hongxiang Zhang; Yao Lu; Yanyan Wang; Wei Pang; Hao Zhang; Xuexin Duan (Micromachines, 2016)
Controlled drug release has a high priority for the development of modern medicine and biochemistry. To develop a versatile method for controlled release, a miniaturized acoustic gigahertz (GHz) resonator is designed and fabricated which can transfer electric supply to mechanical vibrations. By contacting with liquid, the GHz resonator directly excites streaming flows and induces physical shear stress to tear the multilayered polyelectrolyte (PET) thin films. Due to the ultra-high working frequency, the shear stress is greatly intensified, which results in a controlled disassembling of the PET thin films. This technique is demonstrated as an effective method to trigger and control the drug release. Both theory analysis and controlled release experiments prove the thin film destruction and the drug release.